Effects of whitening dentifrices on the enamel color, surface roughness, and morphology = Efecto de los productos de clareamiento sobre el color del esmalte, la rugosidad de la superficie y la morfología - Hazar, Ahmet
The aim of this study was to evaluate the whitening and abrasion effects of dentifrices containing different whitening agents on artificially stained and unstained enamel. 160 human dental enamel discs were distributed into four groups according to the type of dentifrices applied on them (n=40): Group I, non-whitening dentifrice (control group); Group II, dentifrice containing charcoal; Group III, dentifrice containing blue covarine; Group IV, dentifrice containing hydrogen peroxide. Half of the specimens in each group were immersed in coffee solution. Color measurements were evaluated from stained and unstained specimens before and after brushing by a spectrophotometer. The surface roughness of each unstained specimen was analyzed using a profilometer after the brushing and bleaching. The surface of one randomly selected specimen from each group was observed using a scanning electron microscope (SEM). Statistical analysis of the color change was performed using the Kruskal-Wallis test. The one-way ANOVA was used to evaluate surface roughness. Group III provided significantly higher recovery on ΔE00 values than other groups on the unstained enamel (p<0.05). Group IV showed significantly the highest ΔE00 values on stained enamel (p<0.05) and also Group IV showed the highest surface roughness values (p<0.05), SEM revealed a more irregular surface in groups III and IV. It can be stated that dentifrice containing blue covarine is both an effective and a safe way to provide whiter teeth with routine home tooth brushing.